Growth Performance of Swietenia macrophylla King and Azadirachta indica A. Juss. Seedlings Raised in Cocomoss Media and Different Packaging Conditions in Bangladesh - Begum, N.; Rafiqul Haider, M.; Bhomick, N. G.; Azizul Hoque, M. (Indian Forester, 2018)
Growth performance of Swietenia macrophylla and Azadirachta indica seedlings were studied in two containers (polybag and root trainers) with cocomoss media. Simultaneously seedling survival performance was studied in packaging condition with open plastic tray and ventilated paper box. S. macrophylla seedlings raised in polybag showed better performance in comparison to root trainers in terms of survival (87%), height (25.4cm), collar diameter (4.8 mm), biomass production-fresh wt. (6.3gm) and dry wt. (2.0gm) at the age of four months. The difference in height and biomass production was found statistically significant between the containers at 0.01>p level. A. indica seedlings also showed better performance in polybag over root trainers at the age of eight months. In polybag survival (100%), height (24.7 cm), collar diameter (6.5 mm), and biomass production - fresh wt. (10.1 gm) and dry wt. (3.5 gm) was recorded. No significance difference was found between the containers except dry weight at 0.05>p level. Both S. macrophylla and A. indica seedlings raised in polybag showed 100% survival in ventilated paper box, comparatively for longer period than root trainers at the age of eight months.